2017
DOI: 10.3892/ol.2017.6693
|View full text |Cite
|
Sign up to set email alerts
|

L-securinine inhibits the proliferation of A549 lung cancer cells and promotes DKK1 promoter methylation

Abstract: Abstract. L-securinine is a natural product extracted and isolated from the leaf of dried Securinega suffruticosa. The aim of the present study was to explore the effects of L-securinine on proliferation, and the methylation profile of the dickkopf-related protein 1 (DKK1) gene in human lung cancer cells and fibroblasts. L-securinine was extracted, isolated and the structure was identified. The cytotoxicity of L-securinine in A549 cells was evaluated by Cell Counting Kit-8 assays. The expression and DNA methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Pharmacological studies have shown that S. suffruticosa can promote blood circulation, relax the muscles and tendons, invigorate the spleen and kidney, and relieve rheumatic pains. Moreover, this shrub is effective for the treatment of neurasthenia, facial nerve paralysis, post-polio syndrome, dizziness, deafness, narcolepsy, impotence, and acute liver injury, and other diseases [7][8][9][10]. It possesses an extremely high application value [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have shown that S. suffruticosa can promote blood circulation, relax the muscles and tendons, invigorate the spleen and kidney, and relieve rheumatic pains. Moreover, this shrub is effective for the treatment of neurasthenia, facial nerve paralysis, post-polio syndrome, dizziness, deafness, narcolepsy, impotence, and acute liver injury, and other diseases [7][8][9][10]. It possesses an extremely high application value [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sec has been developed as a drug to treat neurological conditions such as ALS, polio, and multiple sclerosis (Buravtseva, 1958). Moreover, recent studies have shown that Sec has inhibitory effects on human lung cancer through cytotoxicity in A549 cells (Han et al, 2017). However, the effect of Sec on bone-resorbing osteoclasts in bone metabolism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the compound induced dose‐dependent downregulation of Dickkopf‐related protein 1 (DKK1) in A549 cells as well as altered methylation of CpG sites in the DKK1 promoter region. Thus, this alkaloid may be a potential antitumor agent that acts by altering the methylation of the DKK1 gene 151 . Furthermore, securinine inhibited both purified thioredoxin and thioredoxin reductase in intact cells 49 .…”
Section: Bioactivities Of Indolizidine Alkaloidsmentioning
confidence: 99%
“…Securinine ( 13 , Figure 4C), a major tetracyclic indolizidine alkaloid isolated from the plant Securinega suffruticosa , has shown anticancer activity in many studies 48,150 . Against A549 lung cancer cells treated for 24, 36, and 48 h, the half‐maximal antiproliferative concentration values of securinine were 8.92, 4.73, and 3.81 μg/ml, respectively 151 . In addition, the compound induced dose‐dependent downregulation of Dickkopf‐related protein 1 (DKK1) in A549 cells as well as altered methylation of CpG sites in the DKK1 promoter region.…”
Section: Bioactivities Of Indolizidine Alkaloidsmentioning
confidence: 99%